1976
DOI: 10.1084/jem.144.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and cellular aspects of xenogeneic mixed leukocyte culture reaction.

Abstract: Xenogeneic lymphocytes can induce proliferative responses in the mixed lymphocyte culture (MLC) ~ which are as strong as those induced by allogeneic lymphocytes (1). It is impossible to determine directly which lymphocyte antigens stimulate the xenogeneic MLC response. The recently described "primed lymphocyte typing" (PLT) assay (2) has made it possible to determine indirectly the genetic control of xenogeneic MLC. Sensitization in a mixed lymphocyte culture positively selects for memory cells which give a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

1979
1979
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 35 publications
3
18
0
Order By: Relevance
“…Early studies indicated that some inter-species T-cell responses, such as human-anti-mouse, could discriminate between individual mouse H-2 haplotypes, suggesting a direct recognition of xenogeneic MHC [18]. Later studies indicated that human responder-type APCs or human cytokines were important for this xenogeneic response, raising the prospect that ‘indirect’ (host APC-dependent) reactivity may be important for the xenogeneic T-cell response [19].…”
Section: Introductionmentioning
confidence: 99%
“…Early studies indicated that some inter-species T-cell responses, such as human-anti-mouse, could discriminate between individual mouse H-2 haplotypes, suggesting a direct recognition of xenogeneic MHC [18]. Later studies indicated that human responder-type APCs or human cytokines were important for this xenogeneic response, raising the prospect that ‘indirect’ (host APC-dependent) reactivity may be important for the xenogeneic T-cell response [19].…”
Section: Introductionmentioning
confidence: 99%
“…These findings suggest that certain T cell subsets require particular cylokincs, which may not be essential for other T eells [15], Moreover, cytokines may be regulated interdependently [11.13] and IL-I, I L-6 and TNF-a are each capable of inducing their own production (for review see 116,17]), These previous studies vv' ere performed on APC-or trtitogcn-activated Teells, The response ofT cells to antigen in a mixed teucoeyto cutture (MLC) rnore etosety mimics in vivo response than mitogen-induced activation, bowever. So far, the rote of APC-derived cytokines produced by human Tcelts whieh are responding to antigen has not been examined, HutTtan T cctts proliferate in response to alloantigen in art MLC in the presenee of responder or stimutator APC [tX 20], However, in a xenogeneic MLC between human T cells and irradiated murine sptenocytes protiferation witi only occur in the presence of responder APC [21]. Previous findings indicate that recotnbinant human (rh) IL-t/( or IL-2 can serve as a secondary signal and thus substitute for APC in order to achieve T cell proliferation in response to murine splenoeytes [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown previously that the cytotoxic cells that are generated in a xenogeneic mixed lymphocyte reaction are of T origin, and recognize specifically H-2 K or H-2 D gene products (10,(16)(17)(18). Furthermore, we have recently observed (a) that the cytotoxic reaction was not inhibited by the presence in the medium of heat-aggregated immunoglobulins, nor by immune complexes and (b) that supernates from xenogeneic mixed leukocyte cultures were unable to induce cytotoxicity either per se or after the addition of naive PBL Xenogeneic Cell-Mediated Lympholysis in Lupus Patients (47) and SLE patients (48).…”
Section: Discussionmentioning
confidence: 99%
“…1). On three occasions, these PBL, educated against DBA/2 spleen cells (H-2d), were also assayed against EL4 targets (H-2b The antigen specificity of the blastogenic response was also checked for both SLE and normal PBL confirming the H-2 restriction already described in cell-according to the method described by Lindhal and mediated xenogeneic reactions (16)(17)(18). Educated PBL Bach (18).…”
Section: Assaymentioning
confidence: 99%